2018
DOI: 10.1101/353581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smoking induces coordinated DNA methylation and gene expression changes in adipose tissue with consequences for metabolic health

Abstract: Abstract

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 86 publications
2
4
0
Order By: Relevance
“…Additionally, three CpG sites within CYP1A1 and RNF122 were identified in both meta-analyses but with different directions of association in cord blood versus placenta. Interestingly, we observed CYP1A1 to be hypomethylated in placenta with exposure to MSDP, which is consistent with studies of adipose, skin, and lung tissues 54 , but this CpG was hypermethylated in the cord blood meta-analysis 10 . Additionally, the most statistically significant association with MSDP in placenta (cg27402634, LEKR1 ) was not associated with MSDP in the cord blood meta-analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, three CpG sites within CYP1A1 and RNF122 were identified in both meta-analyses but with different directions of association in cord blood versus placenta. Interestingly, we observed CYP1A1 to be hypomethylated in placenta with exposure to MSDP, which is consistent with studies of adipose, skin, and lung tissues 54 , but this CpG was hypermethylated in the cord blood meta-analysis 10 . Additionally, the most statistically significant association with MSDP in placenta (cg27402634, LEKR1 ) was not associated with MSDP in the cord blood meta-analysis.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, DNA methylation response to maternal smoking in pregnancy was not mirrored at the transcriptional level of nearby genes. Similarly, previous studies in former smokers have shown that smoking has a longer-lasting influence on the methylome compared to the transcriptome [67]. The reversal rate of gene expression at 1 year after smoking cessation has been calculated in > 50% and reaches > 85% after 10 years, whereas for methylation, it ranges from 17 to 33% with some effects still visible 40 years after smoking cessation.…”
Section: Discussionsupporting
confidence: 56%
“…The rapidly emerging literature shows the methylation alterations in the promoter regions of CYP1B1 in several tumors, including prostate cancer (Tokizane et al, 2005), acute lymphoblastic leukemia (DiNardo et al, 2013) and gastric carcinoma (Kang et al, 2008). Furthermore, hypo-methylated CYP1B1 was up-regulated in current smokers (Tsai et al, 2018). Therefore, silencing of CYP1B1 via promoter methylation by MECP2 overexpression might be another explanation for its protective effects against CSE-induced epithelial cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, bioinformatics analyses by Cao et al identified CYP1B1 as a potential target in smoking-mediating malignancies (Cao et al, 2015). Experimental analysis further demonstrated that hypo-methylated CYP1B1 was up-regulated in current smokers (Tsai et al, 2018). Overexpression of CYP1B1 is considered to be aggressive therapeutic target in advanced nonsmall cell lung cancer (Su et al, 2009).…”
Section: Introductionmentioning
confidence: 99%